Bacteriology and Antimicrobial Resistance in Vanuatu: January 2017 to December 2019 - Nicola D. Foxlee; Nicola Townell; Mary Ann L. Tosul; Lachlan McIver; Colleen L. Lau (MDPI AG, 2020)
The World Health Organization has identified surveillance as a key objective in the containment of antimicrobial resistance. Local antimicrobial resistance surveillance data are used to generate antibiograms to monitor resistance patterns and inform clinicians in the selection of the appropriate empiric treatment when culture results are pending, or if laboratory diagnosis is unavailable. However, producing robust bacteriology data is challenging for Pacific Island Countries and Territories with limited microbiology laboratory capacity. The aim of this study is to describe pathogen occurrence and antibiotic resistance in specimens cultured at the main referral hospital in Vanuatu. We reviewed specimen culture results for the period from January 1, 2017 to December 31, 2019. Demographic and clinical data were extracted from printed and electronic registers and described and analysed. A total of 5816 specimens were cultured, of which 21% were culture positive. Staphylococcus aureus was the predominant pathogen overall (41%), and 3% of the isolates were the methicillin-resistant Staphylococcus aureus. Escherichia coli and Klebsiella pneumoniae were the most frequently isolated gram-negative pathogens, of which 14% and 26% were extended-spectrum β-lactamase-producing, respectively. Our results suggest there is a need for other Pacific Island Countries and Territories to conduct similar studies. There are gaps in knowledge about antimicrobial resistance in Pacific Island Countries and Territories. Antibiograms based on reliable data will define and inform local and national actions for containing antimicrobial resistance. There is also a need to establish a regional surveillance network to strengthen national efforts and to link surveillance data for collaborative action against antimicrobial resistance.